(untitled) - Regnier, Philippe (Honolulu, 1991)
This book major is introduction about Singapore, a trading emporium: The character of states in south-East Asia : the coupling of trading emporia with vast agrarian hinterlands; The regional function of the Singapore economy; Singapore and regional political cooperation,...
Keywords: ASEAN,Southeast asia,Singapore; Foreign economic relations,Foreign economic relations; Singapore,Southeast asia